THE INFLUENCE OF THE INDONESIAN NATIONAL MOVEMENT IN THE EARLY ISLAMIC MOVEMENT IN MALAYSIA - Warjio Warjio (Universitas Wijaya Kusuma Surabaya, 2022)
This article raises the main question: How was the influence of the Indonesian nationalist movement namely nationalism and Islam in the initial nationalism movement in Malaysia? Using the political history approach of this article reveals this important issue. First, the Indonesian nationalism movement had influenced the nationalist movement in Malaysia through Indonesian political activists to Malaysia, then known as Malaysia. The important results of this article make an important contribution that not only is there a national political connection to the formation of Malaysian independence, but the spirit of nationalism and Islam is united in the influence of the early Islamic nationalist movement in Malaysia.Keywords: Indonesian nationalism movement, nationalism movement in Malaysia, islamic movement, islamic political party